Rancang Bangun Programmable Frequency Generator untuk Wireless Power Transfer berbasis H-bridge MOSFET IRF3205 - Revelino Adli; Sabriansyah Rizqika Akbar; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Wireless energy transfer technology has enormous potential, in the field of transportation, for example, to charge a running vehicle. Many variables can affect the efficiency of energy transfer that occurs, one of the discussions in previous research by Akbar, S., et. al. (2021) regarding wireless power transfer, namely the effect of entering the frequency value on the value of the power transferred through a particular wireless power transfer circuit. In this study a frequency generator is made to output a signal that can be used in a wireless power transfer circuit. This research discusses the engineering of the generator frequency using a microcontroller, to produce a PWM signal with a certain frequency, and an IRF3205 Dual Motor MOSFET H-bridge to convert it into an AC signal. The engineered system also uses button and screen interaction with the user as well as monitoring the power drawn by the WPT circuit with the sensor. Based on testing, the system has succeeded in delivering energy and the effects can also be seen at different frequencies. For the output of the system itself, there is an average frequency error value of 0.27% and a maximum error value of 1.01% at a frequency of 121kHz.